Literature Review: The Relationship Of Dietary Patterns With The Incident Of Hypertension In Pregnant Women - Muh. Dwiki Darmawan; Nasrudin Andi Mappaware; Amelia Abdullah; Nur Rakhmah; Aryanti R. Bamahry (Jurnal EduHealth, 2024)
Background:Hypertension in pregnancy is one of the causes of morbidity and death throughout the world for both mother and fetus. Hypertension in pregnancy is defined as the presence of blood pressure of 140 mmHg or more after 20 weeks of pregnancy in women who were previously normotensive, or an increase in systolic pressure of 30 mmHg and diastolic pressure of 15 mmHg above normal values. During pregnancy or breastfeeding, mothers must pay attention to the food they consume. Nutritious food is food that contains energy substances, building substances and substances that meet nutritional needs. This nutritious food meets the needs of the fetus and increases breast milk production.Objective:This literature review aims to determine the relationship between diet and the incidence of hypertension in pregnant women. Method: This research uses the Literature Review method with a Narrative Review design. Scientific articles or journals were obtained from PubMed, Garuda Portal and Google Scholar with specified keywords and inclusion and exclusion criteria. Results:Of the 16 articles obtained, each article was described and criticized, and then research results were obtained which had the same results, namely that there was a relationship between diet and the incidence of hypertension in pregnant women. Conclusion: There is a relationship between diet and the incidence of hypertension in pregnant women.